Prototype Sistem Penilaian Kinerja Karyawan Berbasis Web dengan Metode Behaviorally Anchored Rating Scale (BARS) untuk Peningkatan Objektivitas dan Transparansi - Marta Ardiyanto; Ridwan Dwi Irawan; Kresna Agung Yudhianto (Pusat Riset dan Inovasi Nasional, 2025)
This study develops a web-based employee performance evaluation prototype using the Behaviorally Anchored Rating Scale (BARS) method in higher education institutions. The system reduces evaluator subjectivity through behavior-specific indicators and weighted scoring. Rapid Application Development (RAD) was applied, supported by continuous stakeholder feedback. Reliability testing of the questionnaire showed a Cronbach’s Alpha of 0.850, indicating strong consistency. Core features include behavior indicator management, evaluation visualization, and weighted score calculation. Findings show the system enhances objectivity, transparency, and accountability in performance appraisal.